The Association Between Life Events and Incidence of Hypertension Among Government Employees in China: A Prospective Cohort Study - Ouyang, Feiyun; He, Jun; Cheng, Xunjie; Qiu, Dan; Li, Ling; Bangura, Joseph Benjamin; Duan, Yanyin; Luo, Dan; Xiao, Shuiyuan (Frontiers in Psychology, 2022)
Background: Hypertension (HTN) is a global public health concern. However, the association between life events (LEs) and HTN is complex. Thus, we conducted a prospective cohort study to explore this complex association. Methods: A total of 8077 government employees without HTN were recruited through cluster sampling between 2018 and 2019 in Hunan Province, China. At baseline, information regarding sociodemographic characteristics, LEs, and behavioral factors was collected. After the one-year follow-up, the participants were revisited to obtain the HTN diagnosis. Crude and adjusted Poisson regression models were constructed to calculate the incidence rate ratios (IRRs) and 95% confidence intervals (CIs). Cubic regression spline models were used to visualize the trends between LEs and HTN IRRs. Interactive and subgroup analyses were also performed. Results: The one-year HTN incidence rate among government employees in Hunan province was 4.30% (95% CI: 3.86% to 4.74%). LEs were associated with a higher HTN risk (IRR, 1.02; 95% CI, 1.00 to 1.04). When calculating positive and negative LEs scores separately, only the latter was a risk factor for HTN incidence (IRR, 1.04; 95% CI, 1.03 to 1.06); conversely, positive LEs reduced the risk (IRR, 0.90; 95% CI, 0.85 to 0.96). Compared with patients in the lowest quartile of LEs score, those in quartiles two (IRR, 1.28; 95% CI, 0.96 to 1.71), three (IRR, 1.43; 95% CI, 1.04 to 1.96), and four (IRR, 1.73; 95% CI, 1.26 to 2.37) were at progressively higher risk. In restricted spline curves, a nonlinear association was noted between LEs and HTN risk. Regarding the subcategories of LEs, work-related LEs, personal LEs, and all subcategories of negative LEs were associated with an increased risk of HTN . However, among positive LEs, only the family-related cases were associated with a lower risk of HTN. Conclusion: LEs had a non-linear association with an increased risk of HTN. Negative LEs were risk factors for HTN incidence, whereas positive LEs reduced the risk of HTN. Thus, the importance of LEs should be highlighted in the development of HTN prevention strategies and initiatives.